A mixed method study to determine the attitude of Australian emergency health professionals towards patients who present with deliberate self-poisoning - Martin, C.; Chapman, Rose (2014)
Introduction: Deliberate self-poisoning is one of the frequent presentation types to emergency departments. It has been reported that attitudes of emergency staff may have negative consequences for the wellbeing of the self-poisoning patient. Aim: Determine the attitude of nursing and medical staff towards patients who present with deliberate self-poisoning and to identify if differences exist between the two groups. Design: Mixed-method. Methodology: The "Attitudes towards Deliberate Self-Harm Questionnaire" was distributed to all nursing and medical staff who had direct patient contact at three emergency departments (N= 410). Total and factor scores were generated and analysed against variables age, gender, length of experience working in the emergency department, level of education and by profession. Two open ended questions asked staff to write their perceptions and stories about patients who deliberate self-poison and were analysed using qualitative data analysis. Results: Forty-five percent of staff returned the questionnaire. The attitude of emergency nurses and doctors was positive towards patients who deliberately self-poison. Doctors had significantly higher total and Factor 2 'dealing effectively with the deliberate self-poisoning patient' scores than nurses. After adjusting for length of time working in the emergency department only Factor 2 'dealing effectively with the deliberate self-poisoning patient' remained statistically significant. Staff reported high levels of frustration, in particular to patients who represent. Conclusion/relevance to practice: This information may be used to develop and implement educational strategies for staff to improve the experiences of and better support patients presenting to the emergency department who deliberately self-poison.